Implementation of automatic interleaving and load current sharing techniques using single interleaving bus. Issue 7 (1st June 2016) - Kudtongngam, Jasada; Sangkarak, Kittipong; Lopattanakij, Pakorn; Liutanakul, Pisit; Chunkag, Viboon
Abstract : This study demonstrates automatic interleaving and current sharing techniques with an automatic interleaving system of distributed power supply. Unlike the conventional current sharing techniques, this technique proposes replacing and removing one or more converter modules without interfering with the still‐working interleaved converters. Besides, these techniques are expected to perform a masterless control system and to enable automatic current sharing and phase shifting. A single current waveform on the interleaving bus carries information of the number of modules and phase displacements to perform current sharing and interleaving operations. A four‐phase buck converter prototype was designed, implemented and tested. The replacing and removing modules' scenarios for automatic current sharing and interleaving were demonstrated by the experimental results obtained on the prototype.